Damage assessment of the rolling bearing based on the rigid-flexible coupling multi-body vibration model - Chang, Zhou; Hu, Lai (Manufacturing Technology Journal, 2021)
In the present study, local defects in deep groove ball bearings are studied as forward and inverse problems. To this end, the separation-integration method is applied for modeling the forward problem. It is assumed that the inner race of the rolling element is multi-DOF, while the outer race is deformable along the radial direction. Then the problem is modeled with concepts of the finite element method. The contact force for the rolling elements is described by the nonlinear Hertz contact deformation. Various surface defects originating from local deformations are introduced into the developed model. Since the outer ring can be coupled with the FE model of the housing, the developed bearing model is capable of considering the transmission path of the bearing housing. Then model parameters are modified to reach better performance in predicting local defects. Through translating the inverse problem into the comparison of the geometric distance, measured indicators are used in the defect detection process and the relative location and size of defects are predicted. Finally, the defect range is established to evaluate the fault severity. Obtained results demonstrate that the proposed method is effective and accurate in the studied cases.
Keywords: deep groove ball bearings; quantitative evaluation; the forward and inverse problems; defect range